Independent board of commissioners moderates CSR disclosure relationship on financial performance - Handojo, Natalistyo Tjatur Andi; Machmuddah, Zaky; Sumaryati, Anna (Library of Sultan Agung Islamic University, 2023)
Providing empirical evidence of the role of independent commissioners on the relationship between CSR disclosure and financial performance is the aim of this study. Companies listed on the Indonesian stock exchange are used as the population, but for the sample only companies in the agricultural sector. The sample was obtained using the purposive sampling method, the year of observation was from 2019 to 2021, so that 60 observational data were obtained. The data processing uses Warp PLS version 7.0. The research findings provide evidence that CSR disclosure and independent board of commissioners have an influence on the company's financial performance, besides that the independent board of commissioners also moderates the relationship of CSR disclosure on financial performance. The implication of this research is the importance of the role of independent commissioners in moderating the relationship of CSR disclosure on the company's financial performance.